Volumetric magnetic resonance imaging analysis of multilevel upper airway surgery effects on pharyngeal structure. Issue 12 (20th July 2021) - Sutherland, Kate; Lowth, Aimee B; Antic, Nick; Carney, A Simon; Catcheside, Peter G; Chai-Coetzer, Ching Li; Chia, Michael; Hodge, John-Charles; Jones, Andrew; Kaambwa, Billingsley; Lewis, Richard; MacKay, Stuart; et al.
Abstract: Study Objectives: The Sleep Apnea Multilevel Surgery (SAMS) trial found that modified uvulopalatopharyngoplasty with tonsillectomy (if tonsils present) combined with radiofrequency tongue ablation reduced obstructive sleep apnea (OSA) severity and daytime sleepiness in moderate-severe OSA. This study aimed to investigate mechanisms of effect on apnea-hypopnea index (AHI) reduction by assessing changes in upper airway volumes (airway space, soft palate, tongue, and intra-tongue fat). Methods: This is a case series analysis of 43 participants of 51 randomized to the surgical arm of the SAMS trial who underwent repeat magnetic resonance imaging (MRI). Upper airway volume, length, and cross-sectional area, soft palate and tongue volumes, and tongue fat were measured. Relationships between changes in anatomical structures and AHI were assessed. Results: The participant sample was predominantly male (79%); mean ± SD age 42.7 ± 13.3 years, body mass index 30.8 ± 4.1 kg/m 2, and AHI 47.0 ± 22.3 events/hour. There were no, or minor, overall volumetric changes in the airway, soft palate, total tongue, or tongue fat volume. Post-surgery there was an increase in the minimum cross-sectional area by 0.1 cm 2 (95% confidence interval 0.04–0.2 cm 2 ) in the pharyngeal airway, but not statistically significant on corrected analysis. There was no association between anatomical changes and AHI improvement. Conclusions: This contemporary multilevel upper airway surgery has been shown to be an effective OSA treatment. The current anatomical investigation suggests there are not significant post-operative volumetric changes associated with OSA improvement 6-month post-surgery. This suggests that effect on OSA improvement is achieved without notable deformation of airway volume. Reduced need for neuromuscular compensation during wake following anatomical improvement via surgery could explain the lack of measurable volume change. Further research to understand the mechanisms of action of multilevel surgery is required. Clinical Trial: This manuscript presents a planned image analysis of participants randomized to the surgical arm or the clinical trial multilevel airway surgery in patients with moderate-severe obstructive sleep apnea (OSA) who have failed medical management to assess change in OSA events and daytime sleepiness. https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=266019&isReview=true%20Australian%20New%20Zealand%20Clinical%20Trials%20Registry%20ACTRN12514000338662, prospectively registered on March 31, 2014.